Market opportunities for Florida farmed oysters - Robert Botta; Taryn Garlock; Edward V. Camp; Andrew Ropicki; Frank Asche (EDIS)
The oyster aquaculture industry has grown quickly in recent years. New farming techniques target specific attributes that increase oysters' value and allow them to be sold in the high-value, half-shell market. A lack of economic data makes it difficult for growers to determine which specific attributes increase oyster value, however. This publication summarizes findings from a recent study that examined restaurant menus to obtain economic data on raw, half-shell oysters. Major findings indicate that brand is an oyster attribute that provides value, and that marketing oysters with information on two or more attributes can also result in higher prices. Additionally, locally sourced oysters are often sold at cheaper prices, providing an opportunity for growers from outside regions to enter new markets. The findings will be useful to Florida oyster growers as attempts to expand Florida’s oyster aquaculture industry continue.